TYPES OF MARKETING FUNCTIONS AND ITS ACTIVITIES - Mamasoliyev Rustambek Zafarjon o’g’li; Turg’unboyev Nurislom To’lqin o’g’li; Xaitov Oxunjon Nomoz o’g’li (Scientific Impulse, 2023)
The article is discussed about the Product service management, marketing-information management, pricing, distribution, promotion, and selling are the six marketing functions. These marketing jobs include the tasks that center on comprehending consumers and providing them with the goods they desire. Marketing information management, finance, product and service management, pricing, promotion, selling, and distribution are the seven marketing functions. Each department must collaborate to create a successful marketing strategy in order to support the expansion of your company. The exact definition of functional marketing isn’t set in stone, but it usually refers to focusing on the practical advantages of your business in order to reach particular goals. It attempts to persuade a potential client in a fact-based, intellectual approach.